Medical Management of Ectopic Pregnancy: An Observational Study (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objectives: The aim of this study was to explore the safety and efficacy of medical management of ectopic pregnancy.Materials and methods: This prospective observational study was conducted between February 2011 to August 2013 in Chittagong Medical College Hospital (CMCH) and in different private clinics of Chittagong city. Twenty-seven patients of ectopic pregnancy conceived by fertility treatment were recruited for medical treatment after proper evaluation. Ectopic pregnancy was diagnosed by serum ?-hCG and progesterone level but missing intrauterine pregnancy by transabdominal sonography (TAS). Serum ?-hCG was repeated after 48 hours to observe doubling of the level. If level was not doubled or increment was not at least 66% and serum progesterone level was less than 15ng/ml then it was considered as ectopic pregnancy. Patients were treated with Injection methotrexate 50 mg intramuscularly either by single dose or two doses. After 4 days of 1st injection ?-hCG was repeated and if level decreased > 15% then patients were assessed weekly till ?-hCG fell to